Mortality and glycemic control among patients with diabetes mellitus and uterine or ovarian cancer - Yael N Kusne; Heidi E Kosiorek; Matthew R Buras; Kyle E Coppola; Patricia M Verona; Curtiss B Cook; Nina J Karlin (Future Science OA, 2021)
Aim: To evaluate associations between survival and glycemic control in age-matched patients with endometrial or ovarian cancer, with/without diabetes mellitus (DM). Patients & methods: Patients with newly diagnosed ovarian or endometrial cancer with and without DM were compared. Results: The study included 84 patients with ovarian cancer (28, DM); 96 with endometrial cancer (48 with, 48 without DM). DM patients did not have worse overall or progression-free survival than non-DM patients. Glycemic control was not associated with either cancer. Conclusion: There was no association between DM and survival for patients with uterine or ovarian cancer. In addition, there was no association between uterine and ovarian cancer and glycemic control. Additional studies to confirm these observations in larger populations are required.